Antismoking Centers in Milan's Communal Pharmacies: Analysis of the 2010–2011 Campaign. Issue 5 (September 2013) - Munarini, Elena; Marabelli, Chiara; Marmotti, Aldo; Gardiner, Anna; Invernizzi, Giovanni; Mazza, Roberto; De Marco, Cinzia; Pozzi, Paolo; Boffi, Roberto
Aims and background: According to recent assessments from the Italian Istituto Superiore della Sanità, information and assistance to smokers are still far from satisfactory. We evaluated the impact of a new smoking cessation service located in pharmacies. Smokers' individual characteristics were also considered. Material and Methods: A 1-year pilot study was carried out from October 2010 to September 2011. Five pharmacies in Milan were selected. A psychologist with experience in smoking cessation was present in each pharmacy one afternoon per week, and pharmacists were trained by a team from the Antismoking Center of the Fondazione IRCCS Istituto Nazionale dei Tumori. Each pharmacy was equipped with informative material, carbon monoxide analyzers, and motivational and nicotine dependence questionnaires, in addition to a clinical briefcase. Counseling sessions were also arranged upon request. Results: In the first 12 months of activity, 216 persons asked for a consultation. The sample, aged 15–79 years, reported the following median values: 30 pack/years, 14 ppm CO, and a Fagerström Test of Nicotine Dependence score of 5. More than one-third of the sample (40.3%) had one pathology and 25% had more than one. In some cases (15.7%), people just wanted information about what the service offered. For those who tried to quit, smoking cessation rates were 33.3% at 3 months, 28% at 6 months, and 24.6% at 1 year. Three kinds of pharmacologic therapies were suggested to smokers: nicotine replacement therapy (75.5%), varenicline (17.5%), and bupropion (7%). Conclusions: The results show that an accessible and free smoking cessation service is considered useful by smokers as demonstrated by the large number of requests compared with other smoking centers in Italy. Increased involvement of pharmacists in supporting smoking cessation makes this a promising initiative for the near future.